Halal Certification for Micro And Small Industries of The Food and Beverage Sector In East Jakarta City, Bekasi City, and Gresik Regency - Mohammad, Wily; Ryca Maulidiyah, Nabilla (International Journal of Social Service and Research, 2021)
Halal certification is the one of the most important criteria for Muslims in buying food and beverage. The purpose of this research is to find out the numbers of halal certification among the micro and small industries of the food and beverage sector in East Jakarta City, Bekasi City, and Gresik Regency in running their business. The benefit of this research is that there is certainty and safety for Muslims with halal certification in these three cities in Indonesia, and as the recommendations for the government, academics, and halal activist. The type of this research is descriptive quantitative. The population in this research is the total of micro and small industries in these three cities. Determination of the sample in this research using the Taro Yamane sampling technique, with a significance level of 95%. From the results of these calculations, 395 industries are selected for the research samples. The results of this research are from 395 samples of micro and small industries of the food and beverage sector in East Jakarta City, Bekasi City, and Gresik Regency, 339 (86,8%) are not halal certified. Based on the interview with some samples, there is a lack of understanding, information, and trust in halal certification. It is recommended to academics, government, and halal activists to provide socializations for information and teaching for these industries about halal certification.